Analysis of the Impact of Economic Growth in South Africa from 2000 to 2022 - Annisa Tri Hapsari; Siti Fatimah Nurhayati (Universitas Muhammadiyah Surakarta, 2025)
Purpose: The purpose of this study is to analyze the effect of foreign direct investment (FDI), inflation, average length of schooling, and unemployment rate on economic growth in South Africa from 2000 to 2022.Methodology: This study uses secondary data sourced from the World Bank from 2000 to 2022. The analysis model used in this study is multiple linear regression using the Partial Adjustment Model (PAM) method.Results: The analysis shows that there are two influential variables, namely inflation, which has a negative effect, and average length of schooling, which has a positive effect on South Africa's economic growth, while foreign direct investment (FDI) and unemployment rate have no effect on South Africa's economic growth. The F-test results show that FDI, inflation, average length of schooling, and unemployment rate have a combined effect on economic growth; in other words, the model exists.Applications/Originality/Value: The results of this study are expected to assist key stakeholders, particularly the South African government, in formulating effective and sustainable economic development policies that are adaptive to external shocks, such as global crises and inflationary pressures.